Penerapan discharge planning berbasis leaflet untuk meningkatkan pemahaman pasien - Septawan, Siarizky Cahyaharta; Setyowati, Lilis (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Discharge planning is a crucial component of nursing care to ensure continuity of care after a patient is discharged from the hospital. However, its implementation in the field is often suboptimal, resulting in a lack of comprehensive understanding of the discharge process for patients and families. Purpose: To determine the effectiveness of using leaflets in improving patient and family understanding of the discharge process. Method: The study used a quasi-experimental design with a non-equivalent pretest–posttest design. The sample was selected using a purposive sampling technique, with 12 respondents in the pretest phase and 14 in the posttest phase. The intervention consisted of discharge planning education through leaflets distributed over three days. Data were collected using a questionnaire that had been tested for content validity and reliability. Data analysis was performed using the Chi-Square test with a significance level of p < 0.05. Results: Before the intervention, only 4 respondents (33.3%) understood the discharge process, while 8 respondents (66.7%) did not. After the intervention, understanding significantly increased, with 12 respondents (85.7%) understanding the discharge process, while only 2 respondents (14.3%) still did not (p < 0.05). Conclusion: The leaflet media was shown to significantly improve the understanding of patients' families. Keywords: Discharge Planning; Leaflet; Patient Education; Patient Understanding. Pendahuluan: Discharge planning merupakan komponen penting dalam asuhan keperawatan untuk memastikan kesinambungan perawatan setelah pasien pulang dari rumah sakit. Namun, pelaksanaannya di lapangan seringkali belum optimal, sehingga pasien dan keluarga tidak memahami alur perpulangan secara menyeluruh. Tujuan: Untuk mengetahui efektivitas penggunaan media leaflet dalam meningkatkan pemahaman pasien dan keluarga mengenai alur perpulangan. Metode: Penelitian menggunakan desain quasi-eksperimental dengan non-equivalent pretest–posttest design. Sampel dipilih menggunakan teknik purposive sampling dengan jumlah responden 12 orang pada tahap pre-test dan 14 orang pada tahap post-test. Intervensi berupa edukasi discharge planning melalui media leaflet yang diberikan selama 3 hari. Data dikumpulkan menggunakan kuesioner yang telah diuji validitas isi dan reliabilitasnya. Analisis data dilakukan menggunakan uji Chi-Square dengan tingkat signifikansi p < 0,05. Hasil: Sebelum intervensi, hanya 4 responden (33.3%) yang memahami alur perpulangan, sedangkan 8 responden (66.7%) tidak memahami. Setelah intervensi, tingkat pemahaman meningkat signifikan menjadi 12 responden (85.7%) yang memahami alur perpulangan, sementara hanya 2 responden (14.3%) yang masih belum memahami (p < 0.05). Simpulan: Media leaflet terbukti memberikan peningkatan yang signifikan terhadap pemahaman keluarga pasien. Kata Kunci : Discharge Planning; Edukasi Pasien; Leaflet; Pemahaman Pasien.